The UN local communities and Indigenous peoples' platform: A traditional ecological knowledge‐based evaluation. (15th February 2019) - Shawoo, Zoha; Thornton, Thomas F.
Abstract : This review evaluates the potential of the proposed local communities and Indigenous peoples' platform to effectively engage traditional ecological knowledge (TEK) for climate policy. Specifically, we assess the platform's potential to enable greater representation and participation of Indigenous peoples (IPs) within the United Nations Framework Convention on Climate Change (UNFCCC). An analytical framework based on the extensive TEK and environmental management literature is developed, with a set of criteria identified against which to evaluate the platform. We find that although the process of designing the platform appears to be inclusive of Indigenous views, the structure itself does not recognize the roles that unequal power relations and colonialism play in marginalizing IPs. Limited attention is paid to the institutional barriers within the UNFCCC and the drawbacks of pursuing knowledge "integration" as an end in itself. Based on this, recommendations for improving the platform structure are put forward including using a rights‐based framing, giving greater decision‐making power to IPs, and developing mechanisms to ensure the holistic integrity of TEK and build the overall resilience of climate mitigation and adaptation systems. This article is categorized under: Social Status of Climate Change Knowledge > Sociology/Anthropology of Climate Knowledge